Synthesis of ternary carbide and carbonitride MAX phase particles with controlled dimensions

By using carbon precursors and salts of specific shapes and sizes, combined with solid-state reaction routes, synthesis of structured MAX phase particles at medium temperatures, solving the difficulty in adjusting MAX shape and high-temperature synthesis in the prior art requires high energy. 问题,实现了受控结构的MAX相和MXene颗粒的生产。

CN119451910APending Publication Date: 2025-02-14CENT NAT DE LA RECH SCI (C N R S) +1

Patent Information

Application Number
CN202380049142.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-24
Filing Date
2023-06-23
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to adjust and control the shape/morphology of the MAX phase at the nanoscale, resulting in high energy input required when synthesising MAX phase particles at high temperatures and it is difficult to prepare low-dimensional MAX phase substrates.

Method used

By using carbon or carbon/nitrogen precursors with specific shapes and sizes, such as carbon flakes, carbon rods, carbon fibers, graphene and carbon nanotubes, combined with salt use and solid-state reaction routes, at medium temperatures (e.g. 1000°C). or lower) Synthesize structured MAX phase particles.

Benefits of technology

The production of MAX phase and MXene particles with controlled structures at the micro/nanoscale is achieved, reducing energy input during synthesis and allowing large-scale production of low-dimensional MAX phase particles, including nanosheets and nanorods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451910A_ABST
    Figure CN119451910A_ABST
Patent Text Reader

Abstract

A structured MAX phase particle having the basic formula Mn + 1AXn (I) wherein "M" corresponds to at least one transition metal, "A" is a Group A element, "X" is C or CN, and "n" is equal to 1, 2, 3 or 4 wherein the MAX phase structured particle at least partially has a defined shape is disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of structured MAX phase particles and methods for their preparation. Background Art

[0002] MAX phases are a large class of materials with more than 150 different compositions that have been extensively studied during the past 25 years. n+1 AX n ”, where “M” corresponds to a transition metal, “A” is a group A element, “X” is C and / or N, and “n” is equal to 1, 2, 3 or 4 [1]. MAX phases are mainly prepared by solid-state chemical routes at synthesis temperatures T ≥ 1100 °C (typically 1300 °C-1700 °C) and higher, and are carried out under a protective atmosphere to avoid oxidation [1-7]. Therefore, these synthesis methods require high energy input.

[0003] They have a layered structure and a unique combination of properties that bridge the boundary between metallic and ceramic materials [2]. Many applications are currently being investigated for MAX phases, including replacements for graphite in high-temperature applications, heating elements, high-temperature foil bearings, gas burner nozzles, tools for dry drilling of concrete, ignition devices, and electrical contacts [1].

[0004] MAX phases are also precursors for the synthesis of 2-dimensional (2D) materials called MXenes. MXenes were discovered in 2010 by the groups of Gogotsi and Barsoum [3-6]. MXenes are 2-D metal carbides and nitrides that are formed by etching the A element from the MAX precursor to form a 2D material of formula M. n+1 X n The excellent properties of MXenes in terms of conductivity, surface area, 2-D surface reactivity, etc. make MXenes attractive for a wide range of applications, ranging from energy storage (batteries, supercapacitors), electrocatalysis to medical (photothermal therapy), communications (electromagnetic shielding), gas separation, water purification and dialysis [7]. The rise of MXenes has promoted interest in MAX synthesis, and the preparation of MXenes is the main application of MAX phases today. In particular, non-toxic and environmentally friendly titanium-based MXenes constructed from abundant elements and their blends and composites with polymers, ceramics and metals are attracting considerable attention [7]. MAX powders are commercially available from many manufacturers, including Millipore Sigma.

[0005] The properties of MAX phases and related MXenes depend on the composition, structure, and morphology of the MAX. For example, it is well known that the properties of MXenes depend on their morphology: n+1 Xn ) compared to dozens of layers of M n+1 X n The exfoliated multilayer MXenes that are constructed have low energy storage capacity. However, while the composition of the MAX phase can be tuned by choosing the right precursor ratio (M:X:A), there are no synthetic methods for MAX phases today that allow tuning and controlling the shape / morphology of the MAX at the nanoscale due to the synthetic routes used today. For example, bulk MAX phase particles are mainly prepared using ceramic techniques and grinding with particle sizes > 1 μm without any control over the morphology. The successful preparation of MAX phase substrates with low dimensionality, such as 2-D (flakes) or 1-D (rods), would be a major achievement. These new structures would i) change the properties of the MAX phase due to smaller diffusion distances and electron confinement, larger surface area (…), and ii) allow the direct preparation of 2-D or 1-D MXenes with improved properties from 2-D or 1-D MAX precursors. Summary of the invention

[0006] The object of the present invention is to produce MAX phase and / or MXene particles with controlled structure, in particular controlled morphology and / or size at the micrometer / nanometer scale, and / or to achieve their synthesis with moderate energy input, such as at moderate temperatures (e.g., 1000°C or less). Another object of the present invention is to provide a scalable method for producing the above particles, and in particular low-dimensional MAX phase particles (including MAX phase nanoflakes and MAX phase nanorods), directly from metal powders and / or metal nitrides that are ultimately combined with carbon precursors, in particular in bulk. These particles are of course another object of the present invention.

[0007] By using selected carbon or carbon / nitrogen precursors, at least one of these objectives, and preferably all, is met. It has been found that using such precursors of specific shapes and sizes in specific synthesis methods will provide such particles. DETAILED DESCRIPTION

[0008] The present invention provides a method for obtaining a n+1 AX n (I) wherein "M" corresponds to a transition metal, "A" is a Group A element, "X" is C or CN, and "n" is equal to 1, 2, 3 or 4, the method comprising the steps of:

[0009] a) providing a mixture of M, A and a structuring precursor comprising, consisting of or consisting essentially of C;

[0010] b) subjecting the mixture to a heating step at a temperature ranging from 600°C to 1200°C, preferably from 700°C to 1100°C, even more preferably from 800°C to 1050°C, so as to obtain structured MAX phase particles;

[0011] c) cooling the MAX phase particles; and

[0012] d) Finally, the particles are washed to remove impurities.

[0013] Preferably, the structured precursor is selected from the group consisting of carbon flakes, carbon rods, carbon fibers, carbon lattice rods, carbon tubes, graphene, reduced graphene oxide, single-walled carbon nanotubes, multi-walled carbon nanotubes and aggregates thereof. The use of graphene (especially reduced graphene oxide) and carbon nanotubes (especially single-walled nanotubes) is particularly preferred. The reduced graphene oxide is preferably an aerogel, which can be obtained by freeze-drying a graphene oxide hydrogel (obtained by heating an aqueous dispersion of graphene) and then heating it under an inert atmosphere (e.g., up to 900° C.) to remove oxygen groups.

[0014] About Formula M n+1 AX n , M is particularly selected from the group consisting of at least one of Sc, Ti, V, Cr, Zr, Nb, Mo, Hf and Ta, preferably Ti. n+1 AX n , A is particularly selected from the group consisting of at least one of Al, Si, P, S, Ga, Ge, As, Cd, In, Sn, Ti, Pb and their nitrides; preferably Al or AlN.

[0015] The elements M and A and the structuring precursor are generally in the form of powders. At least M and the structuring precursor are advantageously used in stoichiometric amounts, and the mixture of M, A and the structuring precursor is preferably subjected to a grinding process, for example by ball milling.

[0016] According to a particularly preferred aspect of the present invention, before and / or during the heating step b), a salt is used and admixed into the mixture of M, A and the structured precursor. Further advantageously, before adding the M element and / or the A element, the structured precursor and the (eutectic) salt are premixed together. This premixing step can be carried out by ball milling (especially if the precursor is a thin sheet or sheet such as graphene) or by ultrasonic treatment (especially if the precursor is a rod or tube such as a nanotube). In the latter case, the ultrasonic treatment is carried out in water and the mixture is dried (e.g., freeze-dried) before mixing with M and / or A.

[0017] Preferred salts are selected from the group consisting of NaCl, KCl, LiCl, MgCl2, LiBr, NaBr, MgBr2, KBr, CsCl, BaCl2 and mixtures thereof. Eutectic mixtures such as NaCl and KCl, LiCl and KCl and CsCl and KCl, and BaCl2 and NaCl are preferred. Alternatively, salts such as KBr can be used alone. Mixtures of NaCl and KCl, particularly in a molar ratio of 1:1, are particularly preferred.

[0018] Salts can be widely used as additive materials to produce the MAX phase particles of the present invention, and in particular to produce 1-D and 2-D MAX phase particles. The advantages of using salts in the synthesis are 1) providing better mixing of the raw materials to increase homogeneity, and 2) creating a molten bath at the temperature of forming the MAX phase to accelerate the diffusion rate of the M element.

[0019] The salts used to produce the particles of the present invention, and in particular the 1-D and 2-D MAX phases, are not limited to mixtures of NaCl:KCl, nor are they limited to chloride salts. The salts contemplated are those that 1) do not decompose at 1100°C and 2) do not react with M, A and X and the target MAX phases. Various examples of salts and salt mixtures that can be used as additive materials are listed in Table 1 below.

[0020] Table 1

[0021]

[0022] The heating step or solid state reaction step is carried out at a temperature in the range of 600°C to 1200°C, preferably 700°C to 1100°C, even more preferably 800°C to 1050°C, to obtain structured MAX phase particles. For cost and environmental reasons, it is of course advantageous to use temperatures in the lower range. The selection of a temperature of about 900°C ± 5% has been shown to be particularly effective.

[0023] The heating step is preferably carried out under an inert atmosphere such as Ar. The residence time can be selected in the range of 1 h to 12 h. A preferred residence time range is 3 to 10 hours. When a temperature of about 900°C ± 5% is selected, a residence time of about 5.5 to 6.5 hours is preferred. The heating rate can be about 600°C / h. Once the solid state reaction state has occurred, the mixture containing the MAX phase particles of the present invention can be allowed to cool at room temperature.

[0024] In particular when salts are used, it may be desirable to wash the MAX phase particles. Such a washing step can be effectively performed using (deionized) water. Another suitable solvent for the salt used may also be considered. Additionally or alternatively, the MAX phase particles may be subjected to an acid (e.g. HCl) in order to remove traces of unreacted metal or intermetallic alloys. The acid is then removed, for example using (deionized) water. Once the MAX phase particles have been washed and / or rinsed, they may be dried using commonly known techniques such as gentle heating and / or vacuum.

[0025] The invention also relates to powders of structured MAX phase particles and / or MAX phase particles obtained or obtainable by the process of the invention. Due to their specific and unique structure, such particles or powders exhibit unique properties in the field of materials or electrochemistry, which are closely linked to their production process.

[0026] Another object of the present invention is a kind of formula M n+1 AX n (I) wherein "M" corresponds to a transition metal, "A" is an A group element, "X" is C or CN, preferably C, and "n" is equal to 1, 2, 3 or 4. The particle of the invention is "structured", that is, it has a shape that is not completely random and is at least partially a given and recognizable shape. This shape can be selected from the group consisting of: flakes, sheets, plates, wafers, rods, fibers, filaments, lattice rods, bundles, tubes, and arrays, networks, clusters or aggregates thereof.

[0027] Advantageously, the particles of the invention are structured such that one of their three dimensions is significantly larger than at least one of the other dimensions. By dimensions is meant the dimensions of the major axis, the median axis and the minor axis of the particle.

[0028] Advantageously, the particles of the invention are structured as flakes or aggregates of flakes. Such flakes or flakes may present two of their three dimensions that are significantly larger than the remaining one.

[0029] Alternatively, the particles of the invention may be structured as rods or fibers or networks, clusters or aggregates of rods or fibers. Such rods or fibers may present only one of their three dimensions that is significantly larger than the remaining two.

[0030] "Substantially larger" means that the ratio of the largest dimension to the smallest dimension is at least 10, preferably at least 20, more preferably at least 50, even more preferably 100, and even more preferably at least 300.

[0031] According to a preferred aspect of the present invention, the size of the Max phase particles or powders of the present invention is micrometer-sized or smaller, that is, the average size of the particles is less than 100 μm, preferably less than 50 μm.

[0032] It is further highly preferred that the MAX phase particles or powders of the present invention are:

[0033] - nanoparticles (particle size less than 100 nm),

[0034] - particles with one dimension outside the nanoscale (one-dimensional nanomaterials (1D)), such as nanotubes, nanorods, nanofibers and nanowires; or

[0035] - Particles with two dimensions outside the nanometer scale. (Two-dimensional nanomaterials (2D)) have a sheet-like structure (nanoflakes or nanoplates) with lateral dimensions greater than 100 nm, while the thickness is in the nanometer scale, typically less than 20 nm, preferably less than 5 nm.

[0036] It will be appreciated that when referring to powders, the preferred size of the particles is the mode value and can be measured using laser diffraction techniques.

[0037] To determine the size and dimensions of these particles, the skilled person has access to known techniques, such as analysis of images obtained using a transmission electron microscope (TEM), a scanning electron microscope (SEM) or an atomic force microscope (AFM). These techniques can also be used to determine the size and dimensions of powders, especially nanoscale powders.

[0038] About Formula M n+1 AX n , M is particularly selected from the group consisting of at least one of Sc, Ti, V, Cr, Zr, Nb, Mo, Hf and Ta, preferably Ti.

[0039] About Formula M n+1 AX n , A is particularly selected from the group consisting of at least one of Al, Si, P, S, Ga, Ge, As, Cd, In, Sn, Ti, and Pb; preferably Al.

[0040] The MAX phase particles or powders of the present invention preferably have the following basic formula: Ti2CdC, Sc2InC, Sc2SnC, Ti2AlC, Ti3AlC2, Ti3AlCN, Ti2GaC, Ti2InC, Ti2TlC, V2AlC, V2GaC, Cr2GaC, Ti2GeC, Ti2SnC, Ti2PbC, V2GeC, Cr2AlC, Cr2GeC, V2PC, V2AsC, Ti2SC, Zr2InC, Zr2TiC , Nb2AlC, Nb2GaC, Nb2InC, Mo2GaC, Zr2SnC, Zr2PbC, Nb2SnC, Nb2PC, Nb2AsC, Zr2SC, Nb2SC, Hf2InC, Hf2TlC, Ta2AlC, Ta2GaC, Hf2SnC, Hf2PbC, Hf2SC, Hf2AlC, Hf3AlC2, Zr2AlC, Ti2ZnC, V2ZnC, Nb2CuC, Mn2GaC, or Mo2AuC.

[0041] The MAX phase particles or powders of the present invention preferably have the following basic formulas: Ti3AlC2, Ti2AlC and Ti3AlCN.

[0042] The MAX phase particles or powders of the present invention preferably have the following basic formula: Ti2AlC or Ti3AlC2.

[0043] Another object of the present invention is a method for obtaining structured MXene particles, for example, MXene particles having the following formula (II), wherein the structured MAX phase particles or powders of the present invention are subjected to an acid treatment, such as with hydrofluoric acid, preferably in aqueous solution. Other acids may also be used, such as NH4HF2, LiF in HCl, LiCl in HF, or mixtures thereof.

[0044] Another object of the present invention is a structured MXene particle having the formula (II) Mn+1XnT, wherein "M" corresponds to at least one transition metal, "X" is C or CN, "T" is at least one synthetically defined surface end group (including but not limited to -O, -OH, -F, or -Cl), and "n" is equal to 1, 2, 3 or 4, wherein the structured MXene particle at least partially has a defined morphology and size as described above for the MAX phase particles, and / or the structured MXene particle is obtained or obtainable by the method of the present invention. The nature of the T group depends on the environment and chemicals used during the etching process. For example, when aqueous LiF+HCl electrolyte is used to etch the A element of the MAX phase to prepare MXene, T can be -O, -OH, -F, which is a result of surface oxidation of the MXene. The T group is bound to the surface M and may be bound to the X atom. The structured MXene particle may have a defined shape selected from the group consisting of: rods, sheets, plates, fibers, filaments, tubes, lattice rods and aggregates thereof. In particular, the structured MXene particles may not be in the shape of flakes. Also, the structured MXene particles may not be in the shape of flakes and plates and / or flakes and sheets and / or flakes, plates and sheets.

[0045] Another object of the present invention is the use of the structured MAX phase particles of the present invention in the manufacture of graphite in high temperature applications, heating elements, high temperature foil bearings, gas burner nozzles, tools for dry drilling of concrete, ignition devices, electrical contacts or structured MXene particles.

[0046] Another object of the present invention is the use of the structured MAX phase particles of the present invention in the manufacture of energy storage devices (such as batteries, supercapacitors), electrocatalytic devices, medical devices (such as for photothermal therapy), communication devices (for example for electromagnetic shielding), gas separation devices, water purification devices and dialysis devices.

[0047] Yet another object of the present invention is the use of structured nanoparticles such as graphene sheets and nanotubes in the manufacture of MAX phases and MXene particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] The following drawings are presented for illustrative purposes only and should not be considered to limit the scope of the present invention in any way.

[0049] Figure 1 : shows the XRD pattern of the MAX phase nanosheets synthesized in Example 1;

[0050] Figure 2 : SEM images of (a) rGO precursor and (bd) MAX phase nanosheets of Example 1 at different magnifications are shown;

[0051] Figure 3 : TEM and high-resolution TEM images of the 2D MAX phase nanosheets of Example 1 are shown;

[0052] Figure 4 : shows the chemical composition estimated by EDS analysis of the MAX phase nanoflakes of Example 1;

[0053] Figure 5 : shows the XRD pattern of the Ti3AlC2 MAX phase nanosheets synthesized in Example 2;

[0054] Figure 6 : SEM images of 2-D Ti3AlC2 MAX phase nanosheets of Example 2 at different magnifications are shown;

[0055] Figure 7 : shows the XRD pattern of 1D Ti2AlC MAX phase nanorods synthesized in Example 3;

[0056] Figure 8 : SEM images of (a) SWCNT precursor and (b) and (c) 1-D Ti2AlC MAX phase nanorods of Example 3 are shown;

[0057] Fig. 9 : TEM and high-resolution TEM images of 1-D Ti2AlC MAX phase nanorods of Example 3 are shown;

[0058] Fig.10 : shows the chemical composition estimated by EDS analysis of the 1-D Ti2AlC MAX phase nanorods of Example 3;

[0059] Fig.11 : shows the XRD pattern of the 1-D Ti2AlC MAX phase nanorods of Example 4;

[0060] Fig.12 : SEM images of 1-D Ti2AlC MAX phase nanorods of Example 4 at different magnifications (a: 2 µ, b: 200 nm);

[0061] Fig.13 : shows the chemical composition estimated by EDS analysis of the 1-D Ti2AlC MAX phase nanorods of Example 4;

[0062] Fig.14 : shows the XRD pattern of the 2-D Ti2AlC MAX phase nanosheets of Example 5;

[0063] Fig.15: SEM images of the 2-D Ti2AlC MAX phase nanosheets of Example 5 at different magnifications (a: 5 µ, b: 20 µ, c: 500 nm);

[0064] Fig.16 : shows the chemical composition estimated by EDS analysis of the 2-D Ti2AlC MAX phase nanoflakes of Example 5;

[0065] Fig.17 : The Ti2AlC MAX phase precursor and Ti2CT of Example 6 are shown x XRD pattern of MXene;

[0066] Fig.18 : shows the Ti2CT of Example 6 x SEM and TEM images of MXene at different magnifications (a: 1 µ, b: 200 nm, c: 20 nm).

[0067] Example 1: Synthesis of 2-D Ti at 1000°C n+1 AlC n MAX-phase nanosheets

[0068] Ti metal powder (99.9% purity, about 325 mesh), Al metal powder (99.9% purity, about 325 mesh), and reduced graphene oxide (rGO, lab-made aerogel) were used as starting materials. The synthesis method was divided into three steps: 1) carbon precursor synthesis, 2) solid-state reaction, followed by 3) post-reaction washing process.

[0069] 1) Carbon precursor synthesis

[0070] The preparation of rGO precursor is described in detail as follows. Graphene oxide (GO) aqueous dispersion was prepared by a modified Hummers method following the published literature [8. Advanced Materials [Advanced Materials], 2019, 31(8): 1805075]. Then the GO aqueous dispersion with a concentration of 2 g / L was sealed in a hydrothermal reactor and heated to 160°C for 6 hours to form rGO hydrogel. The rGO hydrogel was frozen by liquid nitrogen and then freeze-dried to obtain rGO aerogel. Afterwards, the rGO aerogel was placed in a tubular furnace and heated to 900°C and kept under Ar atmosphere for 60 minutes to further remove the oxygen groups of rGO. The heating rate was 600°C / h.

[0071] 0.1 g of 2-D rGO precursor and eutectic salt (NaCl: KCl = 1: 1, molar ratio) were mixed in a weight ratio of 1: 30. The mixture was ground with a mortar and pestle in the presence of ethanol for 1 h. Ball milling mixing technique can be applied to scale up the process. Then 0.797 g of Ti metal powder was added to the mixture and ground for 10 min; 0.27 g of Al metal powder was added to the mixture and ground for 10 min. The molar ratio of Ti: Al: C was 2: 1.2: 1. Excess Al was used to improve the purity of the MAX phase. A ratio of 1 would result in the formation of more TiC. The mixture was then dried at 80 °C under vacuum for 1 h. The mixture was then placed in a corundum boat crucible and covered with 5 g of eutectic salt (NaCl: KCl = 1: 1, molar ratio).

[0072] 2) Solid-state reaction steps

[0073] The crucible was placed in a tube furnace and heated to 1000°C under Ar atmosphere with a residence time of 1 h. The heating rate was 600°C / h. The mixture was then cooled naturally to room temperature.

[0074] 3) Post-reaction washing process steps

[0075] The mixture was immersed in 200 ml of deionized water for 30 minutes to form an aqueous suspension. The suspension was then vacuum filtered and washed three times with deionized water to remove residual salts. The obtained mixture was then added to 100 ml of 6 M HCl and stirred for 6 h to complete the washing and remove unreacted metal or intermetallic alloy traces (i.e., intermetallic compounds), such as TiAl. The suspension was then vacuum filtered and washed three times with deionized water to remove residual acid. Finally, the obtained product was dried at 80 ° C under vacuum for at least 2 h before material characterization.

[0076] Characterization

[0077] X-ray diffraction analysis of 2-D MAX phase nanoflakes was performed using a D-8 diffractometer (Endeavor, Bruker) under Cu-Kα radiation (40 kV, 25 mA). The XRD patterns were recorded from 7° to 80° in the 2θ range with a step size of 0.01° and a collection time of 1 s per step. The microstructure and chemical composition of 2-D MAX phase nanoflakes and go precursors were analyzed by scanning electron microscopy (SEM-FEG, JSM-7900F, at 5 kV) together with energy dispersive spectroscopy (EDS, BRUKER XFLASH 6-60, at 15 kV) and transmission electron microscopy (TEM, JEM-2100F, at 200 kV).

[0078] Figure 1 The XRD pattern of the as-prepared MAX phase is presented. A mixture of Ti3AlC2 (312) and Ti2AlC (211) phases was identified, and the successful preparation of the MAX phase was confirmed. The 312 phase has a larger unit cell and a longer diffusion length than the 211 phase; therefore, the formation of the 312 Ti3AlC2 phase generally requires a higher temperature than the 211 Ti2AlC MAX phase.

[0079] By estimating the crystallite size of the 211 and 312 MAX phases using the Scherrer equation based on the (002) peak, 55 nm and 37 nm were obtained for the 211 MAX phase and 312 MAX phase, respectively.

[0080] In previous solid-state reactions, higher temperatures (1300°C) were required to form the Ti3AlC2 MAX phase. In the present method, a significant amount of Ti3AlC2 MAX phase was obtained at 1000°C. This highlights the importance of the selected 2-D carbon precursor, which significantly shortens the diffusion distance when forming the MAX phase. The presence of the molten salt promotes the transport of reagents, making liquid phase and interfacial transport of reagents possible.

[0081] The ratio of 312 to 211 MAX phases can be adjusted by controlling the ratio of the starting materials and the solid-state reaction time (see Example 2). A small amount of Tic was also detected, which could be eliminated by extending the reaction time.

[0082] The morphology of the synthesized rGO is shown in Figure 2 a. Thin carbon flakes were formed and used as carbon precursors for MAX synthesis. The morphology and microstructure of the obtained MAX phase nanoflakes are shown in Figure 2 b and Figure 2 c and Figure 3a. The typical flake morphology of the MAX phase is observed. The morphology of the 2-D rGO precursor is retained to form the target MAX phase. The length and width of these flakes range from a few micrometers to tens of micrometers. Figure 2 d shows Figure 2 c is a partial enlargement of the MAX flakes, where the thickness is in the range of tens of nanometers. This result is consistent with the TEM (transmission electron microscopy) analysis ( Figure 3 b), where the thickness of a single MAX phase (along the (002) direction) particle was found to be approximately 30 nm. These results are consistent with the estimated crystallite size from the Scherrer equation. The lattice distance of the obtained MAX phase particles is approximately 0.946 nm, which matches well with the distance of the (002) plane ( Figure 3 c).

[0083] Figure 4 The chemical composition of MAX phase flakes from EDS analysis is presented. The uniform distribution of Ti and Al elements further confirms the successful preparation of MAX phase nanoflakes. The C element is not shown here due to the background noise of the carbon ribbon used in the SEM measurement.

[0084] In summary, 2-D MAX phase nanoflakes were successfully produced by using a solid-state reaction route at 1000°C with a 2-D rGO precursor as the carbon source. The obtained MAX phase is a mixture of Ti3AlC2(312) and Ti2AlC(211) phases; the ratio of 312 to 211 MAX phases is controlled by the synthesis time. The in-plane size of the MAX phase flakes ranges from a few micrometers to tens of micrometers, with a thickness of a few nanometers to tens of nanometers.

[0085] Example 2: Synthesis of 2-D Ti3AlC2 MAX phase nanosheets at 1000°C

[0086] Ti metal powder (99.9% purity, about 325 mesh), Al metal powder (99.9% purity, about 325 mesh), and reduced graphene oxide (rGO, laboratory-prepared aerogel) were used as starting materials.

[0087] 1) Carbon precursor synthesis

[0088] The preparation of 2-D rGO precursor was generally as detailed in Example 1. 0.025 g of 2-D rGO precursor and eutectic salt (NaCl: KCl = 1: 1, molar ratio) were mixed in a weight ratio of 1: 30. The mixture was ground with a mortar and pestle in the presence of ethanol for 1 h. Ball milling mixing technique can be applied to scale up the process. Then 0.149 g of Ti metal powder was added to the mixture and ground for 10 minutes; 0.034 g of Al metal powder was added to the mixture and ground for 10 minutes. The molar ratio of Ti: Al: C was 3: 1.2: 2. The mixture was then dried at 80°C under vacuum for 1 h. The mixture was then placed in a corundum boat crucible and covered with 3 g of eutectic salt (NaCl: KCl = 1: 1, molar ratio).

[0089] 2) Solid-state reaction steps

[0090] The crucible was placed in a tube furnace and heated to 1000°C under Ar atmosphere with a residence time of 10 h. The heating rate was 600°C / h. The mixture was then cooled naturally to room temperature.

[0091] 3) Post-reaction washing process steps

[0092] The mixture was immersed in 100 ml of deionized water for 30 minutes to form an aqueous suspension. The suspension was then vacuum filtered and washed three times with deionized water to remove residual salts. The obtained mixture was then added to 50 ml of 6 M HCl and stirred for 6 h to complete the cleaning and remove unreacted metals or intermetallic compounds. The suspension was then vacuum filtered and washed three times with deionized water to remove residual acid. Finally, the obtained product was dried at 80 ° C under vacuum for at least 2 h, and the material was analyzed.

[0093] Characterization

[0094] X-ray diffraction analysis of 2-D MAX phase nanoflakes was performed using a D-8 diffractometer (Endeavor, Bruker) under Cu-Kα radiation (40 kV, 25 mA). The XRD patterns were recorded from 7° to 80° in the 2θ range with a step size of 0.01° and a collection time of 1 s per step. The microstructure and chemical composition of 2-D MAX phase nanoflakes and rGO precursors were analyzed by scanning electron microscopy (SEM-FEG, JSM-7900F, at 5 kV) together with energy dispersive spectroscopy (EDS, BRUKER XFLASH 6-60, at 15 kV) and transmission electron microscopy (TEM, JEM-2100F, at 200 kV).

[0095] Figure 5 An XRD pattern of the as-prepared MAX phase is presented. The Ti3AlC2(312) phase was identified and the successful preparation of the MAX phase was confirmed. In the present method, a temperature of 1000°C was used, which is lower than previously used. This highlights the importance of the selected 2-D carbon precursor, which significantly shortens the diffusion length during the solid-state reaction to form the MAX phase. Small amounts of TiC were also detected.

[0096] By using the Scherrer equation based on the (002) peak, the crystallite size of the Ti3AlC2 MAX phase nanoflakes was estimated to be 21 nm.

[0097] The morphology of the synthesized rGO is shown in Figure 2 a. The morphology and microstructure of the obtained MAX phase nanosheets are shown in Figure 6 a and Figure 6 In b, the typical flake morphology of the MAX phase is observed. The morphology of the 2D rGO precursor is retained to form the target MAX phase. The length and width of these flakes range from a few micrometers to tens of micrometers.

[0098] In summary, 2-D Ti3AlC2 MAX phase nanoflakes were successfully produced by using 2-D rGO precursor as carbon source. In the present invention, a temperature of 1000°C was used to initiate the solid-state reaction, which is much lower than the previous solid-state reaction synthesis method (1300°C-1700°C). The in-plane size of the MAX phase flakes ranged from several micrometers to tens of micrometers, with a thickness of tens of nanometers.

[0099] Example 3: Synthesis of 1-D Ti2AlC MAX phase nanorods at 1000°C

[0100] 1-D Ti2AlC MAX phase nanorods were prepared using Ti metal powder (99.9% purity, about 325 mesh), Al metal powder (99.9% purity, about 325 mesh) and single-walled carbon nanotubes (SWCNTs, TUBALL®, from OCSiAl Europe: OCSiAl Ltd, 207 Regent Street, London W1B 3HH, United Kingdom) as starting materials. The specifications of these SWCNTs are as follows:

[0101]

[0102] 1) Raw material preparation steps

[0103] 0.025 g of 1-D SWNCT precursor and eutectic salt (NaCl: KCl = 1: 1, molar ratio) were mixed in a weight ratio of 1: 10. The mixture was immersed in 30 ml of deionized water and subjected to probe sonication for 2 h. The suspension was then frozen by liquid nitrogen and then freeze-dried to obtain a SWCNT / salt mixture. Then, 0.199 g of Ti metal powder and 0.068 g of Al metal powder were added to the mixture and ground with a mortar and pestle in the presence of ethanol for 1 h. Ball milling can be used to scale up. The molar ratio of Ti: Al: C is 2: 1.2: 1. The mixture was then dried at 80°C under vacuum for 1 h. The mixture was then placed in a corundum boat crucible and covered with 3 g of eutectic salt (NaCl: KCl = 1: 1, molar ratio).

[0104] 2) Solid-state reaction steps

[0105] The crucible was placed in a tube furnace and heated to 1000°C under Ar atmosphere with a residence time of 4 h. The heating rate was 600°C / h. The mixture was then cooled naturally to room temperature.

[0106] 3) Post-reaction washing process steps.

[0107] The mixture was immersed in 100 ml of deionized water for 30 minutes to form an aqueous suspension. The suspension was then vacuum filtered and washed three times with deionized water to remove residual salts. The obtained mixture was then added to 50 ml of 6 M HCl and stirred for 6 h to complete the cleaning and remove unreacted metals or intermetallic compounds. The suspension was then vacuum filtered and washed three times with deionized water to remove residual acid. Finally, the obtained product was dried at 80 ° C under vacuum for at least 2 h, and the material was analyzed.

[0108] Characterization

[0109] X-ray diffraction analysis of 1D MAX phase nanorods was performed using a D-8 diffractometer (Endeavor, Bruker) under Cu-Kα radiation (40 kV, 25 mA). The XRD patterns were recorded from 7° to 80° in the 2θ range with a step size of 0.01° and a collection time of 1 s per step. The microstructure and chemical composition of 1D MAX phase nanorods were analyzed by scanning electron microscopy (SEM-FEG, JSM-7900F, at 5 kV) together with energy dispersive spectroscopy (EDS, BRUKER XFLASH 6-60, at 15 kV) and transmission electron microscopy (TEM, JEM-2100F, at 200 kV).

[0110] Figure 7 The XRD patterns of the obtained material after the washing process are presented. The Ti2AlC(211) MAX phase was identified and the successful preparation of the target MAX phase was confirmed. The crystallite size of the Ti2AlC MAX phase nanorods was estimated to be 55 nm by using the Scherrer equation based on the (002) peak.

[0111] like Figure 8 As shown in a, the typical morphology of SWCNTs was observed. Figure 8 b and Figure 8 c presents the morphology of the microstructure of the obtained 1-D Ti2AlCMAX phase. The morphology of the 1-D SWCNT precursor is retained to form the target MAX phase. Nanorods with lengths ranging from a few micrometers to tens of micrometers and widths ranging from tens of nanometers to less than 200 nanometers were observed. This result is consistent with the TEM analysis ( Fig. 9 and Fig. 9 b). These nanorods aggregate to form MAX particles with a size of tens of micrometers; this is due to the aggregation of SWCNT precursors.

[0112] The chemical composition estimated by EDS is shown in Fig.10 The uniform distribution of Ti and Al elements further confirms the successful preparation of MAX phase nanorods. The C element is not shown due to the background noise of the carbon ribbon used in the SEM measurement.

[0113] In summary, 1-D Ti2AlC MAX phase nanorods were successfully produced by using a solid-state reaction route at 1000 °C with 1-D SWCNT precursors as the carbon source. The lengths of the nanorods ranged from a few micrometers to tens of micrometers, and the widths ranged from tens of nanometers to less than 200 nanometers.

[0114] Example 4: Synthesis of 1D Ti2AlC MAX phase nanorods at 900°C

[0115] 1) Raw material preparation steps

[0116] The raw material preparation steps of 1-D Ti2AlC MAX phase nanorods are the same as those described in Example 3.

[0117] 2) Solid-state reaction steps

[0118] The crucible was placed in a tube furnace and heated to 900 °C under Ar atmosphere with a residence time of 6 h. The heating rate was 600 °C / h. The mixture was then cooled naturally to room temperature.

[0119] 3) Post-reaction washing process steps.

[0120] The mixture was immersed in 100 ml of deionized water for 30 minutes to form an aqueous suspension. The suspension was then vacuum filtered and washed three times with deionized water to remove residual salts. The obtained mixture was then added to 50 mL of 6 M HCl and stirred for 6 h to complete the cleaning and remove unreacted metals or intermetallic compounds. The suspension was then vacuum filtered and washed three times with deionized water to remove residual acid. Finally, the obtained product was dried at 80 ° C under vacuum for at least 2 h, and the material was analyzed.

[0121] Characterization

[0122] X-ray diffraction analysis of 1D MAX phase nanorods was performed using a D-8 diffractometer (Endeavor, Bruker) under Cu-Kα radiation (40 kV, 25 mA). The XRD pattern was recorded from 5° to 80° in the 2θ range with a step size of 0.01° and a collection time of 1 s per step. The microstructure of 1D MAX phase nanorods was analyzed by scanning electron microscopy (SEM-FEG, JSM-7900F, at 5 kV) together with energy dispersive spectroscopy (EDS, BRUKER XFLASH 6-60, at 15 kV).

[0123] Fig.11 The XRD patterns of the obtained material after the washing process are presented. The Ti2AlC(211) MAX phase was identified and the successful preparation of the target MAX phase was confirmed. The crystallite size of the Ti2AlC MAX phase nanorods was estimated to be 56 nm by using the Scherrer equation based on the (002) peak.

[0124] Fig.12 a and Fig.12 b presents the morphology of the microstructure of the obtained 1-D Ti2AlC MAX phase. The morphology of the 1-D SWCNT precursor is retained to form the target MAX phase. Nanorods with lengths ranging from a few micrometers to tens of micrometers and widths ranging from tens of nanometers to less than 200 nanometers are observed.

[0125] The chemical composition estimated by EDS is shown in Fig.13 The uniform distribution of Ti and Al elements further confirms the successful preparation of MAX phase nanorods. The C element is not shown due to the background noise of the carbon ribbon used in the SEM measurement.

[0126] In summary, 1-D Ti2AlC MAX phase nanorods were successfully produced by using a solid-state reaction route at 900°C using 1-D SWCNT precursors as carbon sources. In the present invention, a temperature of 900°C was used to initiate the solid-state reaction, which is much lower than the previous solid-state reaction synthesis methods (typically in the range of 1100°C-1700°C). The length of the nanorods ranged from several micrometers to tens of micrometers, and the width ranged from tens of nanometers to less than 200 nanometers.

[0127] Example 5: Synthesis of 2-D Ti2AlC MAX phase nanosheets at 900°C

[0128] Ti metal powder (99.9% purity, about 325 mesh), Al metal powder (99.9% purity, about 325 mesh), and reduced graphene oxide (rGO, laboratory-prepared aerogel) were used as starting materials.

[0129] 1) Carbon precursor synthesis

[0130] The preparation of 2-D rGO precursor was generally as described in detail in Example 2.

[0131] 2) Solid-state reaction steps

[0132] The crucible was placed in a tube furnace and heated to 900 °C under Ar atmosphere with a residence time of 6 h. The heating rate was 600 °C / h. The mixture was then cooled naturally to room temperature.

[0133] 3) Post-reaction washing process steps

[0134] The mixture was immersed in 100 ml of deionized water for 30 minutes to form an aqueous suspension. The suspension was then vacuum filtered and washed three times with deionized water to remove residual salts. The obtained mixture was then added to 50 ml of 6 M HCl and stirred for 6 h to complete the cleaning and remove unreacted metals or intermetallic compounds. The suspension was then vacuum filtered and washed three times with deionized water to remove residual acid. Finally, the obtained product was dried at 80 ° C under vacuum for at least 2 h, and the material was analyzed.

[0135] Characterization

[0136] X-ray diffraction analysis of 2-D MAX phase nanoflakes was performed using a D-8 diffractometer (Endeavor, Bruker) under Cu-Kα radiation (40 kV, 25 mA). The XRD patterns were recorded from 5° to 80° in the 2θ range with a step size of 0.01° and a collection time of 1 s per step. The microstructure and chemical composition of 2-D MAX phase nanoflakes and rGO precursors were analyzed by scanning electron microscopy (SEM-FEG, JSM-7900F, at 5 kV) together with energy dispersive spectroscopy (EDS, BRUKER XFLASH 6-60, at 15 kV).

[0137] Fig.14 The XRD pattern of the as-prepared MAX phase nanoflakes is presented. The Ti2AlC(211) phase was identified and the successful preparation of the MAX phase with a solid-state reaction temperature of 900°C was confirmed. The crystallite size of the Ti2AlC MAX phase nanorods was estimated to be 57 nm by using the Scherrer equation based on the (002) peak. A small amount of TiC was also detected.

[0138] The morphology of the synthesized rGO is shown in Figure 2 a. The morphology and microstructure of the obtained MAX phase nanosheets are shown in Fig.15 a. Fig.15 b and Fig.15 In c, the typical flake morphology of the MAX phase is observed. The morphology of the 2D rGO precursor is retained to form the target MAX phase. The length and width of these flakes range from a few micrometers to tens of micrometers.

[0139] The chemical composition estimated by EDS is shown in Fig.16 The uniform distribution of Ti and Al elements further confirms the successful preparation of MAX phase nanosheets. The C element is not shown due to the background noise of the carbon ribbon used in the SEM measurement.

[0140] In summary, 2-D Ti2AlC MAX phase nanoflakes were successfully produced by using 2-D rGO precursor as carbon source. In the present invention, a temperature of 900°C was used to initiate the solid-state reaction, which is much lower than the previous solid-state reaction synthesis method (1300°C-1700°C). The in-plane size of the MAX phase flakes ranged from several micrometers to tens of micrometers, with a thickness of tens of nanometers.

[0141] Example 6: MXene prepared from 2-D Ti2AlC MAX phase nanosheets

[0142] The 2-D Ti2AlC MAX phase nanoflakes from Example 5 were used as a catalyst for preparing Ti2CT by using aqueous hydrofluoric acid solution. xPrecursors of MXene.

[0143] 0.15 g of Ti2AlC MAX phase precursor was added to 7.5 mL of etchant. The etchant consisted of 0.75 mL of concentrated HF (50 wt.%), 4.5 mL of concentrated HCl (37 wt.%), and 2.25 mL of deionized water. The mixed solution was stirred at 35 °C for 3 h. After the etching reaction occurred, the product was washed with deionized water by repeated centrifugation at 10000 rpm for 4 minutes until pH 6 was reached. Then, Ti2CT x The MXene suspension was frozen by liquid nitrogen and then freeze-dried to obtain MXene powder.

[0144] Characterization

[0145] Ti2CT x X-ray diffraction analysis of MXene was performed using a D-8 diffractometer (Endeavor, Bruker) under Cu-Kα radiation (40 kV, 25 mA). The XRD patterns were recorded from 5° to 80° in the 2θ range with a step size of 0.016° and a collection time of 0.13 s per step. The Ti2CT4O3 was characterized by scanning electron microscopy (SEM-FEG, JSM-7900F, at 5 kV) and transmission electron microscopy (TEM, JEM-1400, at 200 kV). x The microstructure of MXene was analyzed.

[0146] Fig.17 A Ti2AlC MAX precursor and a Ti2CT prepared as x XRD pattern of MXene. Most of the diffraction peaks belonging to the MAX phase disappeared after the reaction, and the (002) peak shifted to a lower 2θ angle, indicating that Ti2CT was successfully prepared from 2-D Ti2AlC MAX phase nanoflakes. x MXene.

[0147] The synthesized Ti2CT x The morphology of MXene is presented in Fig.18 a; After the etching reaction, MAX flakes are broken into smaller MXene particles. Fig.18 b and Fig.18 c shows the obtained Ti2CT x The microstructure of MXene, in which the typical MXene feature with an interlayer spacing of 1.01 nm was observed, further proving the successful preparation of Ti2CT x MXene.

[0148] Example 7: Proposed method for preparing 2-D Ti3AlCN MAX phase nanosheets at 1000°C

[0149] Ti metal powder (99.9% purity, about 325 mesh), aluminum nitride (AlN) powder (99% purity, about 325 mesh), and reduced graphene oxide (rGO, lab-made aerogel) were used as starting materials. The synthesis method was divided into three steps: 1) carbon precursor synthesis, 2) solid-state reaction, followed by 3) post-reaction washing process.

[0150] 1) Carbon precursor synthesis

[0151] The preparation of rGO precursor is described in detail as follows. GO aqueous dispersion can be prepared by a modified Hummers method following the published literature [AdvancedMaterials, 2019, 31(8): 1805075]. Then the GO aqueous dispersion with a concentration of 2 g / L can be sealed in a hydrothermal reactor and heated to 160°C for 6 hours to form rGO hydrogel. The rGO hydrogel will be frozen by liquid nitrogen and then freeze-dried to obtain rGO aerogel. Afterwards, the rGO aerogel is placed in a tubular furnace and heated to 900°C and kept under Ar atmosphere for 30 minutes to remove the oxygen groups of rGO. The heating rate is 600°C / h.

[0152] 0.025 g of 2-D rGO precursor and eutectic salt (NaCl: KCl = 1: 1, molar ratio) were mixed in a weight ratio of 1: 30. The mixture was ground with a mortar and pestle in the presence of ethanol for 1 h. Note that ball milling mixing technology can be applied for large-scale production. Then 0.300 g of Ti metal powder was added to the mixture and ground for 10 minutes; 0.103 g of AlN powder was added to the mixture and ground for 10 minutes. The molar ratio of Ti: Al: C: N is 3: 1.2: 1: 1.2. The mixture was then dried at 80°C under vacuum for 1 h. The mixture was then placed in a corundum boat crucible and covered with 3 g of eutectic salt (NaCl: KCl = 1: 1, molar ratio).

[0153] 2) Solid-state reaction step

[0154] The crucible was placed in a tube furnace and heated to 1000°C under Ar atmosphere with a residence time of 6 h. The heating rate was 600°C / h. The mixture was then cooled naturally to room temperature.

[0155] 3) Post-reaction washing process steps

[0156] The mixture was immersed in 100 ml of deionized water for 30 min to form an aqueous suspension. The suspension was then vacuum filtered and washed three times with deionized water to remove residual salts. The final product would be 2-D Ti3AlCN MAX phase nanosheets.

[0157] References

[0158] [1] Deysher, Grayson, et al. “Synthesis of Mo4VAlC4 MAX-phase and two-dimensional Mo4VC4 MXene with five atomic layers of transition metals.” ACS nano 14.1 (2019): 204-217.

[0159] [2] Gonzalez‐Julian, Jesus. “Processing of MAX-phases: From synthesis to applications.” Journal of the American Ceramic Society 104.2 (2021): 659-690.

[0160] [3] US Patent 9,193,595, M. Barsoum, Y. Gogotsi, MN Abdelmalak,O. Mashtalir, Compositions Comprising Free-Standing Two-Dimensional Crystals.PCT / US12 / 43273, WO Patent 2,012,177,712, filed June 20, 2012.

[0161] [4] US Patent 9,415,011, M. Barsoum, Y. Gogotsi, MN Abdelmalak,O. Mashtalir, Compositions Comprising Free-Standing Two-Dimensional Crystals.Issued Aug. 16, 2012

[0162] [5] U.S. Patent 9,415,570, M. Barsoum, Y. Gogotsi, M. N. Abdelmalak,O. Mashtalir, Compositions Comprising Free-Standing Two-Dimensional Crystals.Issued Aug. 16, 2016

[0163] [6] U.S. Patent 9,837,182, M. Barsoum, Y. Gogotsi, M. N. Abdelmalak,O. Mashtalir, Compositions Comprising Free-Standing Two-Dimensional Crystals.Issued Dec. 5, 2017

[0164] [7] Vahid Mohammadi, Armin, Johanna Rosen, and Yury Gogotsi. "Theworld of two-dimensional carbides and nitrides (MXenes)." Science 372.6547(2021).

[0165] [8] Chong Luo, Wei Lv, Changsheng Qi, Lixiang Zhong, Zheng-Ze Pan,Jia Li, Feiyu Kang, and Quan-Hong Yan Advanced Materials, 2019, 31(8):1805075.

Claims

1. A basic formula M n+1 AX n (I) structured MAX phase particles, wherein "M" corresponds to at least one transition metal, "A" is a Group A element, "X" is C or CN, and "n" is equal to 1, 2, 3 or 4, wherein the MAX phase structured particles at least partially have a defined shape.

2. The structured MAX phase particles according to claim 1, wherein The defined shape is selected from the group consisting of flakes, rods, sheets, plates, fibers, filaments, tubes, lattice rods, and aggregates thereof.

3. The structured MAX phase particles according to claim 1, wherein The particles have a size of micrometers or less.

4. The structured MAX phase particles according to claim 3, wherein: The particles are nanoparticles; 1D nanomaterials, such as nanotubes, nanorods, nanofibers, nanowires or aggregates thereof; or 2D nanomaterials having a sheet-like structure, such as nanosheets, nanoplates or aggregates thereof.

5. The structured MAX phase particles according to any one of claims 1 to 3, wherein The particles are preferably flakes, rods, aggregates containing rods or aggregates containing flakes.

6. The structured MAX phase particle according to any one of claims 1 to 5, wherein In formula (I), M is Ti and / or A is Al, and / or X is C.

7. The structured MAX phase particles according to any one of claims 1 to 6, wherein Formula (I) is Ti2AlC or Ti3AlC2.

8. A method of obtaining structured MAX phase particles having a basic formula Mn+1AXn (I), wherein "M" corresponds to a transition metal, "A" is an A-group element, "X" is C or CN, and "n" is equal to 1, 2, 3 or 4, the method comprising the steps of: a) providing a mixture of M, A and a structuring precursor comprising, consisting of or consisting essentially of C; b) subjecting the mixture to a heating step at a temperature ranging from 600°C to 1200°C, preferably from 700°C to 1100°C, even more preferably from 800°C to 1050°C, so as to obtain structured MAX phase particles; c) cooling the MAX phase particles; and d) Finally, impurities are removed.

9. The method according to claim 8, wherein: The structured precursor is selected from the group consisting of carbon flakes, carbon rods, carbon fibers, carbon lattice rods, carbon tubes, graphene, reduced graphene oxide, single-walled carbon nanotubes, multi-walled carbon nanotubes, and aggregates thereof.

10. The method according to any one of claims 7 to 9, wherein: The mixture is further admixed with a salt before and / or during the heating step b).

11. The method according to claim 10, wherein: The salt is selected from the group consisting of NaCl, KCl, LiCl, MgCl2, LiBr, NaBr, MgBr2, KBr, CsCl, BaCl2 and mixtures thereof, such as NaCl and KCl, LiCl and KCl and CsCl and KCl, and BaCl2 and NaCl.

12. The method according to claim 11, wherein: The salt mixture is selected from the group consisting of a NaCl and KCl mixture, preferably in a 50 / 50 molar ratio, a LiCl and KCl mixture, preferably in a 60 / 40 molar ratio, a CsCl and KCl mixture, preferably in a 62.5 / 37.5 molar ratio, and a BaCl2(40) and NaCl(60) mixture, preferably in a 40 / 60 molar ratio.

13. A method for obtaining structured MXene particles, wherein: The structured MAX phase particles obtained according to any one of claims 1 to 7 or according to any one of claims 8 to 12 are subjected to an acid treatment, preferably by contact with HF, NH4HF2, LiF in HCl or LiCl in HF.

14. A compound having the formula (II): M n+1 X n T, wherein "M" corresponds to at least one transition metal, "X" is C or CN, "T" is a surface end group such as -O, -OH, -F or -Cl, "n" is equal to 1, 2, 3 or 4, wherein the structured MXene particles at least partially have a defined shape and / or the structured MXene particles are obtained by the method according to claim 13, and wherein the defined shape is selected from the group consisting of: rods, sheets, plates, fibers, filaments, tubes and lattice rods.

15. Use of structured MAX phase particles according to any one of claims 1 to 7 or obtained according to the method of any one of claims 8 to 12 in the manufacture of graphite for high temperature applications, heating elements, high temperature foil bearings, gas burner nozzles, tools for dry drilling of concrete, ignition devices, electrical contacts, or structured MXene particles.

Citation Information

Patent Citations

  • Compositions comprising free-standing two-dimensional nanocrystals

    US9193595B2

  • Compositions comprising free-standing two-dimensional nanocrystals

    US9415570B2

  • Compositions comprising free-standing two-dimensional nanocrystals

    US9837182B2

Cited By

  • Conductive reinforced phase material and in-situ preparation method thereof

    CN121911870A

  • MAX series material with cross-scale geometric structure and template-oriented preparation method of MAX series material

    CN122464422A